PREDICTION OF CURRENCY CRISES USING A FISCAL SUSTAINABILITY INDICATOR - CRUZ-RODRIGUEZ,ALEXIS (ILADES. Universidad Alberto Hurtado., 2011)
The purpose of this paper is to investigate whether a fiscal sustainability indicator (FSI) can be used as a leading indicator to predict currency crises. Firstly, the sustainability of the fiscal policy in 17 developing countries is analysed using a FSI developed by Croce and Juan-Ramón (2003). Then, the FSI is evaluated in order to help predict currency crises. Using a nonlinear Markov-switching model, and applying the Gibbs sampling approach, it is found that the FSI influences the probability of entering a currency crisis period. Also, in the absence of official definitions for currency crises, different definitions are used to evaluate whether they induce different results in the analysis. In general, the results highlight how an unsustainable fiscal position leads to the eventual collapse of the exchange rate in some developing countries.